2016
DOI: 10.1002/pmic.201500196
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analyses of the interaction between the plant‐growth promoting rhizobacterium Paenibacillus polymyxa E681 and Arabidopsis thaliana

Abstract: Plant growth-promoting rhizobacteria (PGPR) facilitate the plant growth and enhance their induced systemic resistance (ISR) against a variety of environmental stresses. In this study, we carried out integrative analyses on the proteome, transcriptome, and metabolome to investigate Arabidopsis root and shoot responses to the well-known PGPR strain Paenibacillus polymyxa (P. polymyxa) E681. Shoot fresh and root dry weights were increased, whereas root length was decreased by treatment with P. polymyxa E681. 2DE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 61 publications
1
37
0
2
Order By: Relevance
“…In contrast, Kwon et al (2016) found that some of the proteins related to the glycolysis pathway, such as FBA and pyruvate dehydrogenase complex component E2, were significantly up-regulated by the PGPR strain P. polymyxa E681 in Arabidopsis roots. Carbohydrate metabolism provides the plant with required carbon, which is critical for the production of new tissues, and also can have profound effects on plant growth through modulation of cell division and expansion (Eveland and Jackson, 2012; Kwon et al, 2016). In this study, we found that the application of P. polymyxa NSY50 increased the abundance of FRK, ENO, BFRUCT, and ATPase compared to control conditions.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In contrast, Kwon et al (2016) found that some of the proteins related to the glycolysis pathway, such as FBA and pyruvate dehydrogenase complex component E2, were significantly up-regulated by the PGPR strain P. polymyxa E681 in Arabidopsis roots. Carbohydrate metabolism provides the plant with required carbon, which is critical for the production of new tissues, and also can have profound effects on plant growth through modulation of cell division and expansion (Eveland and Jackson, 2012; Kwon et al, 2016). In this study, we found that the application of P. polymyxa NSY50 increased the abundance of FRK, ENO, BFRUCT, and ATPase compared to control conditions.…”
Section: Discussionmentioning
confidence: 89%
“…tomato DC3000 in Arabidopsis (Jones et al, 2006) and were increased in response to various hormones, such as salicylic acid, ethylene, methyl jasmonate, and auxin, and to biotic and abiotic stress (Lieberherr et al, 2003; Faltin et al, 2010). Additionally, Kwon et al (2016) found that four glutathione S-transferases were significantly up-regulated by plant-growth-promoting rhizobacterium P. polymyxa E681 in Arabidopsis and suggested that the activation of defense-related proteins may the reason for resistance to the fungal pathogen. It was reported that the overexpression of GSTs induced by another PGPR, P. fluorescens , had an essential role in the ISR by priming rice plants and protecting cells from oxidative damage (Kandasamy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…polymyxa имеет сложные специфические взаимоотношения с растением-хозяином на моле-кулярно-генетическом уровне. Так, сообщалось о стимуляции ферментативной активности хити-назы и β-1,3-D-глюканазы [6], глюкозо-6-фосфат дегидрогеназы, глутатион редуктазы и глутатион S-трансферазы [7,8] в растениях, инокулиро-ванных P. polymyxa. Повышение хитиназной и β-1,3-D-глюканазной активности в растениях, как известно, коррелирует с резистентностью к фитопатогенам.…”
Section: Effect Of Exopolysaccharides Of the Bacteriumunclassified
“…Повышение хитиназной и β-1,3-D-глюканазной активности в растениях, как известно, коррелирует с резистентностью к фитопатогенам. К числу ферментов, играющих важную роль в повышении устойчивости рас-тений к различным стрессам, относят и белки с антиоксидантными свойствами, индуцируемые ризобактериями P. polymyxa [8]. К примеру, были идентифицированы 10 белков с такими свой-ствами (среди них -тиоредоксин редуктаза 2, глутатион пероксидаза 6, пероксидаза 43) и по-казано повышение их активности в корнях и побегах Arabidopsis thaliana, инокулированных ризосферным штаммом P. polymyxa E681 [8].…”
Section: Effect Of Exopolysaccharides Of the Bacteriumunclassified